The Influence of Store Layout, Product Diversity, and Product Quality on Purchasing Decisions at Viera Souvenir Shop in Pekanbaru - Manisa Leila; Endang Sutrisna (IAIN Palopo, 2021)
Purchasing decisions are an important part of the product marketing concept and this is the background of this research. Store layout, product diversity and product quality are part of the factors supporting consumer purchasing decisions. This study aims to find out and analyze the influence of store layout, product diversity and product quality on purchasing decisions at Viera Souvenirs Pekanbaru. This research is a descriptive study using a quantitative approach. The analysis method used in this study is simple and multiple linear regression analysis, and by going through validity tests and reliability tests. In this study, the results obtained were that: 1) Store Layout has a positive and significant effect on Purchasing Decisions, 2) Product Diversity has a positive and significant effect on Purchasing Decisions, 3) Product Quality has a positive and significant effect on Purchasing Decisions, and 4) Store Layout, Product Diversity and Product Quality have a positive and significant effect on Purchasing Decisions at Viera Souvenirs Pekanbaru.